Analisis Pengaruh Literasi Keuangan, Kemudahan Penggunaan dan Gaya Hidup terhadap Minat Generasi Z dalam Menggunakan Dompet Digital (Go-Pay) - Nurhaeni Nurhaeni; Erin Soleha (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
People's perceptions can shift from traditional (paper money) transactions to digital money transactions due to the conveniences and benefits of digital wallets. The purpose of this study is to ascertain whether Generation Z's interest in using a digital wallet (Go-Pay) is influenced by their lifestyle, financial literacy, and ease of use. A sample of respondents from the Z generation in the Bekasi Regency were used for the quantitative research method. A questionnaire was used for data collection. Accidental sampling was used, and the Lemeshow formula was used for the purposive sampling method. Validity, reliability, R-square, Stone-Geisser Q-square, and t tests are the analytical methods utilized. by making use of the tool for analysis known as PLS. This study found that Generation Z's interest in using the Go-Pay digital wallet application is not influenced by their level of financial literacy; rather, Generation Z's interest is influenced by their lifestyle and the ease of use of the application